PENGARUH WORK-LIFE BALANCE DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN : (PADA PERAWAT RUMAH SAKIT PERMATA CIREBON) - Melly Melly; Sari Laelatul Qodriah; Risdianto Risdianto (Jurnal Administrasi Terapan, 2025)
This study aims to analyse the influence of work-life balance and job satisfaction on nurse performance at Permata Hospital, Cirebon. The background of this study is based on the increasing work demands of healthcare workers, which often give rise to problems such as work-life imbalance, low job satisfaction, and emotional stress, ultimately leading performance decline. This study used a quantitative approach, with a population of 90 nurses at Permata Hospital, Cirebon, and data collection was conducted using a questionnaire. Data analysis employed validity, reliability, normality, multiple linear regression, t-tests, and f-tests, utilizing IBM SPSS 25. The validity test results showed that all statement items were valid, with a calculated r value greater than the r table value (0.281). The results of the multiple linear regression analysis showed that work-life balance (X1) had a positive and significant effect on performance (Y) with a significance value of 0.008 (<0.05) and a regression coefficient of 0.184, while job satisfaction (X2) also had a positive and significant effect on performance (Y) with a significance value of 0.000 (<0.05) and a regression coefficient of 0.516. This proves that both variables have a significant effect on nurse performance. Simultaneously, the f-test results also show that work-life balance and job satisfaction have a positive and significant effect on employee performance. Thus, it can be concluded that the performance of nurses at Permata Cirebon Hospital is determined by work-life balance and job satisfaction which complement each other, where job satisfaction has a more dominant influence. This study provides implications that hospital management needs to design policies that support work-life balance. personal well-being and improving job satisfaction to maintain the quality of healthcare services and organizational sustainability. Keywords: Work-Life Balance, Job Satisfaction, and Employee Performance.